The Relationship between Perpendicular Management and Mastery of Memorizing Al-Qur'an in Haflah Khatmil Qur'an Activities - Al Asy'ari, Abdurrohman; El Syam, Robingun Suyud (Al-Hayat: Journal of Islamic Education, 2024)
This paper explores the relationship between perpendicular management and completeness in memorizing the Qur'an, specifically how well perpendicular can motivate, move and evaluate the achievement of learning the Qur'an. With this management, many students remember one year, so studying is enjoyable. A qualitative study with case studies was conducted at PPTQ Al-Asy'ariyyah Wonosobo. Interviews were conducted with the tahfidz teacher and the khaflah khatmil Qur'an activity committee, to ensure the connection between perpendicular management in memorizing the Qur'an and the completeness of memorization. Data analysis techniques apply data collection, presentation, reduction and verification. This study shows that PPTQ Al-Asyariyyah emphasizes vertical management for santri so they quickly complete the memorization of the Qur'an. The steps of perpendicular management include consistency, persistence, focus, regularity, straightness, routine, and commitment. Santri who can apply these steps will complete their memorization more quickly, because perpendicular management has a reciprocal relationship with the completeness of memorizing the Qur'an. The implication of the research is to implement vertical management for tahfidz Qur'an institutions to achieve better results. Research contributes to the development of the tahfidz Qur'an program, particularly in Islamic boarding schools. This study develops its setting and orientation by linking perpendicular management to the completeness of memorizing the Qur'an. This shows the prominent role of vertical management because some instances show that intelligence only guarantees complete memorization of the Qur'an.